PERJANJIAN PERKAWINAN DALAM PERPEKTIF HUKUM PERDATA DAN HUKUM ISLAM - Faruq, Ahmad (Irtifaq, 2018)
Abstract: This article is aimed at discussing the marriage agreements in the perspective of civil law and Islamic law. The fact that there are many divorce rates in Tndonesia result the phenomenon of premarital agreements developing in line with the increasing number of people realizing that marriage is also a financial commitment like the importance of the purpose of marriage itself. As a marriage agreement if it has been agreed upon by the bride and groom, then each is obliged to fulfill it, as long as there is no force the agreement. The content of the agreement must also be not conflict with the Qur'an.. The agreement must not aim at justifying the forbidden or prohibiting the lawful. The marriage agreement does not lie in the essence of the material, but in the commitment that the husband and wife must respect each other, guard and remind him the obligations of the husband and wife so that pre marriage agreements are one of the important things in marriage, both at the time of making the agreement and at the time of application. In daily life.